2018
DOI: 10.1007/s11136-018-1804-9
|View full text |Cite
|
Sign up to set email alerts
|

Computer assistive technology and associations with quality of life for individuals with spinal cord injury: a systematic review

Abstract: Despite the scarcity of studies and their methodological limitations, there is evidence that assistive technology for computer access favors the quality of life of people with tetraplegia due to SCI, since it improves participation, independence, and self-esteem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Assistive technology (AT) is defined by the World Health Organization as ‘systems and services related to the delivery of assistive products and services [that] maintain or improve an individual’s functioning and independence, thereby promoting their well-being’ (World Health Organization, 2018). AT has been shown to improve quality of life for people with a range of different needs including people with neurodevelopmental conditions (Lancioni & Singh, 2014), cognitive impairment and dementia (Klimova et al, 2018), physical disabilities (Baldassin et al, 2018) and the elderly (Agree & Freedman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Assistive technology (AT) is defined by the World Health Organization as ‘systems and services related to the delivery of assistive products and services [that] maintain or improve an individual’s functioning and independence, thereby promoting their well-being’ (World Health Organization, 2018). AT has been shown to improve quality of life for people with a range of different needs including people with neurodevelopmental conditions (Lancioni & Singh, 2014), cognitive impairment and dementia (Klimova et al, 2018), physical disabilities (Baldassin et al, 2018) and the elderly (Agree & Freedman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Specific wheelchair features that influence patient satisfaction include ergonomic components (e.g., arm and head rests), reclining and tilting capabilities, customizable controls, and controls that allow caregivers to operate wheelchairs . However, there is mixed evidence supporting the relationship between quality of life (QOL) and mobility in the ALS population, perhaps because a requirement for assistive technology is associated with reduced independence and more advanced disease …”
Section: Introductionmentioning
confidence: 99%
“…9 However, there is mixed evidence supporting the relationship between quality of life (QOL) and mobility in the ALS population, perhaps because a requirement for assistive technology is associated with reduced independence and more advanced disease. 13,14 While previous studies have shown a favorable effect of mobility on QOL in patients with ALS, others have not supported this relationship. [15][16][17][18] Studies that counter the relationship between mobility and QOL show that social interactions and leisure activities are more important determinants of QOL than mobility.…”
mentioning
confidence: 99%
“…Loss of voluntary upper extremity control alongside preserved cognitive function is common in persons with high spinal cord injuries (SCI), and can result in difficulty operating computers [1, 2]. As computers play an important role in everyday life, and specifically in social participation, the ability to control them can have significant bearing on quality of life (QOL)[3]. In particular, affected individuals may find themselves marginalized and unable to stay maintain social ties.…”
Section: Introductionmentioning
confidence: 99%